Crop water stress index and yield of water-deficit-stressed alfalfa - Hattendorf, M. J.; Carlson, R. E.; Abd Halim, Mohd Ridzwan; Buxton, D. R. (American Society of Agronomy, 1988)
The yield relationship of water-deficit-stressed alfalfa (Medicago sativa L.) with the Crop Water Stress Index (CWSI) may be dynamic over the alfalfa harvest period. This investigation was conducted to define the alfalfa yield-CWSI relationship(s), to test possible advantages of using the CWSI over the canopy-min us-air temperature (Tc-Ta) differential, and to combine the yield-CWSI relationship with a growth function. •Apollo II' alfalfa was grown for 2 yr in 100-L containers set into the ground and protected from rain by a movable shelter. The soil was a Nicollet silt loam topsoil (fine-loamy, mixed, mesic Aquic Hapludoll). Treatments were irrigation levels of 112, 100,88,77, and 65% field capacity. Five harvests were taken at 7-d intervals beginning 21 d 'after an initial clipping. Canopy temperatures were taken daily with an infrared thermometer. A series of exponential yield-CWSI curves resulted from the sequential harvests. Yield reductions of about 10 and 20% resulted from mean CWSI of 0.05 and a.lO, respectively, over 42-d periods. The Gompertz growth function was modified for water-deficit- stress by combining it with the exponential yield-CWSI relationship. Vapor-pressure deficit (VPD) effectively normalized the Tc-Ta data, allowing yield data of the 2 yr to be combined in the yield-mean CWSI relationship. Yield and Tc-Ta data not normalized for VPD showed clear separation by year for slight VPD differences. Alfalfa yield response to water-deficit-stress over time appeared to be adequately described by the combined Gompertz function and the yield-CWSI (Tc+Ta normalized for VPD) curves.